Validasi Komik Matematika Edukatif (Komatif) untuk Siswa Sekolah Dasar - Ayu, Retna Sukma; Maula, Luthfi Hamdani; Kurniasari, Efi (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to develop and validate a learning media in the form of Educational Mathematics Comics (Komatif) as a learning aid for elementary school students, especially on the topic of multiplication. This research uses the Research and Development (RnD) method by adapting the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects include media experts, material experts, and practitioner experts who act as validators, as well as limited trials on 3rd-grade elementary school students. Data were obtained through validation sheets and expert reviews using a Likert scale, then analyzed qualitatively and quantitatively. The validation results show that the comic media received scores from media experts of 93.75%, material experts of 96.42%, and practitioner experts of 92.5%, with an overall average of 94.22%, which falls into the very feasible category. This comic media is considered attractive, communicative, and suitable for the characteristics of elementary school students. In conclusion, Komatif is feasible to be used as an innovative learning media that can increase learning motivation, strengthen conceptual understanding, and foster students' self-confidence by minimizing anxiety towards mathematics.   Keywords: Media Feasibility, Educational Comics, Multiplication Concept, Mathematics, Elementary School